Sulphated mesoporous silica synthesized from rice husk ash for chalcone production - Nor Illiana , Mohd Nor (2012)
Chalcone is an aromatic ketone that have important biological properties. It can be prepared by an aldol condensation between a benzaldehyde and an acetophenone in the presence of catalyst. A series of S-MCM-48 (SO 42 / MCM-48) was synthesized in this study. Rice husk ash (RHA), an agriculture waste was used as a silica (Si0 2 ) source to synthesis the MCM-48 mesoporous molecular sieves by mean of hydrothermal method and suiphation medification using sulfuric acid (H2SO4) as the sulphate sources. The pore packing order of the SO4 2-doped material dependend strongly on the synthesis conditions such as aging temperature, pH of reaction mixture and dopant concentration. The physicochemical properties of mesoporous material was characterized by X-Ray diffraction (XRD), surface area analysis (BET), Fourier- Transform Infrared Spectroscopy (FTIR) and Thermogravimetric Analyzer (TGA). A simple preparation method was used to generate strong acidity catalyst by introducing sulphate groups onto the surface of MCM-48. The prepared sulphated MCM-48 has been used to catalyzed benzaldehyde and acetophenone and was analyzed by using GC. The conversion of acetophenone was calculated and the best conversion was 85.5% by using S-MCM48(60) catalysts.